Postérités du cut-up dans la chanson rock (1970-2000) - Clémentine Hougue (Itinéraires)
Created in 1959 by William S. Burroughs and Brion Gysin, the cut-up technique rests on cutting and assembling scraps of texts from various sources. Burroughs employed it notably in the “Nova trilogy” (The Soft Machine, 1961; The Ticket That Exploded, 1962; Nova Express, 1964). Initially condemned, the cut-up technique inspired many rock musicians and infiltrated mainstream popular culture from the 1970s onward. Therefore, the present article will examine the terms of the “rock posterity” of an experimental writing technique.